Pengaruh Karakteristik Keuangan Perusahaan dan Struktur Kepemilikan Terhadap Return Saham - Ilham Yoga Ananta; Triyono, Triyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of corporate financial characteristics and ownership structure on stock returns in property and real estate companies listed on the Indonesia Stock Exchange (BEI) during the 2020–2022 period. The independent variables tested include profitability (ROA), liquidity (Current Ratio), leverage (DER), managerial ownership, and institutional ownership, while the dependent variable is stock returns. This research uses a quantitative method with multiple linear regression and classical assumption tests to ensure the model's validity. The results indicate that profitability and liquidity do not significantly affect stock returns, while leverage and institutional ownership have a positive impact. Managerial ownership does not significantly influence stock returns. Future research is recommended to focus more on specific industry sectors and consider different ownership structures in influencing stock returns.